2020
DOI: 10.1097/rhu.0000000000001357
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis Patients

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In IPF patients, a positivity for ANCA antibodies may be observed in about 5-10% of cases [4,5]. In particular, anti-MPO antibodies have been reported in 4-36% of patients with idiopathic interstitial pneumonia, including IPF, while the occurrence of MPA has been described in a range from 1.7 to 25.7% of patients [20,21]. This group of patients might be called "pulmonary limited vasculitis" and considered a phenotypic variant of MPA, as reported by Katsumata et al [22].…”
Section: Discussionmentioning
confidence: 99%
“…In IPF patients, a positivity for ANCA antibodies may be observed in about 5-10% of cases [4,5]. In particular, anti-MPO antibodies have been reported in 4-36% of patients with idiopathic interstitial pneumonia, including IPF, while the occurrence of MPA has been described in a range from 1.7 to 25.7% of patients [20,21]. This group of patients might be called "pulmonary limited vasculitis" and considered a phenotypic variant of MPA, as reported by Katsumata et al [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 24 patients with AAV and ILD, it was found that pulmonary function was progressing over time. 145 In addition, ILD presence among patients with MPA appeared to decrease life expectancy by almost 50% 148 and was associated with a 4-fold higher mortality. 149 In a series of 62 French patients with AAV and ILD, the 1-, 3- and 5-year survival rates were 93.5%, 89.6% and 83.8% respectively, with older age at AAV diagnosis, alveolar hemorrhage and UIP pattern being associated with increased mortality.…”
Section: Anca-associated Vasculitis (Aav)mentioning
confidence: 99%
“…Similar to other fibrotic interstitial pneumonias, both isolated ANCA-IIP and AAV-ILD are associated with a restrictive pattern with reduced total lung capacity, forced vital capacity (FVC) and diffusing capacity for carbon monoxide, though co-existing airflow obstruction can occasionally be observed in AAV-ILD [7,8,11,15,16,18,21,26,27,31]. FVC and diffusing capacity have been shown to decline over time [11,26,31].…”
Section: Pulmonary Function Testing and Bal Cellular Findingsmentioning
confidence: 99%
“…Commonly described radiographic imaging patterns of ANCA/AAV-ILD include ground glass opacities, reticulation, interlobular septal thickening, consolidation, nodular pattern and honeycombing [10,15,18,26,27,30,31,32,73]. Airway lesions have also been reported and include bronchiolitis, bronchial wall thickening and bronchiectasis [71,73].…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation